Development of mobile app for food waste reduction - Chia, Glen Zhen Nan (Nanyang Technological University, 2024)
The global demand for food has surged significantly, driven largely by emerging economies and a world population that has doubled in the past century. This demand has increased food wastage in recent years, most notably at the household level, which accounts for 60% of global food waste. In Singapore, approximately 800 million kg of food waste is generated yearly, roughly the size of 1500 Olympic-sized swimming pools. Despite ongoing efforts to mitigate its impact, mounting concerns over its social, economic, and environmental impact have prompted the United Nations to list food waste as a pressing global issue and garnered international attention that spurred many studies to determine its underlying causes in a bid to mitigate its effect. In recent years, mobile applications have seen widespread adoption as a tool for driving sustainability efforts, especially as studies suggest consumer behaviours are a major contributing factor to household food waste. Therefore, to combat this, this project presents the development of a mobile application, SustainEats, aimed at helping Singaporean households reduce food waste. SustainEat features a food storage tracker to monitor item expiration, recipe recommendations to optimise ingredient usage, tips on proper food storing practices, and a platform for food donations. These tools collectively, have encouraged sustainable food consumption and reduced household food waste in Singapore.